Project-Based Learning Model to Improve Understanding of Science Concepts in Fifth-Grade Elementary School Students - Ni Nyoman Rediani; Komang Widiani (Journal of Education Action Reseach, 2026)
Students' conceptual understanding in several schools in Indonesia is still relatively low. Given this condition, this study aims to analyze the Project-Based Learning (PjBL) model to improve fifth-grade students' understanding of science concepts, particularly changes in natural phenomena. The study used a Classroom Action Research (CAR) approach, implemented in several cycles: planning, implementation, observation, and reflection. The subjects of this study were 24 fifth-grade elementary school students, 13 female and 11 male. Data were collected through tests, observations, and documentation, then analyzed quantitatively to assess the effectiveness of the actions. The research data obtained through observations and tests were then processed using a quantitative analysis model. The completion criteria were determined based on the Minimum Completion Criteria (KKM) ≥ 70, with a classical success indicator if at least 75% of students achieved that score. The study's results indicate that implementing PjBL effectively improves students' conceptual understanding. The percentage of classical completion increased from 25% in the pre-cycle to 41.67% in the first cycle, and reached 87.5% in the second cycle. This increase indicates that students' active involvement in contextual projects can deepen conceptual understanding, increase learning motivation, foster collaboration, and develop critical thinking skills. Therefore, PjBL can be used as an effective alternative learning model to improve the quality of understanding of science concepts in elementary schools.